The Importance of Understanding Learning Models for Prospective Agriculture Vocational High School Teachers - Dwi Haryanta; Pramita Laksitarahmi Isrianto; Marmi Marmi; Sunaryo Sunaryo; Endrayana Putut Laksminto Emanuel (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to examine the ability of teacher professional program students to identify instructional problems and formulate effective solutions through classroom action research, and develop a reflective learning model based on classroom action research findings to support teachers’ professional development. This qualitative research design adopted a transcendental phenomenological approach and involved 17 prospective Vocational High School (VHS) teachers participating in the Teaching Practicum Program in Purwosari, Pasuruan, and Gondang, Nganjuk. They were selected purposively based on data accessibility. Data were collected through classroom observations and semi-structured interviews and analyzed to identify patterns in problem identification, instructional decision-making, and the effectiveness of learning models implemented. The results showed that teachers improved their teaching practices by implementing student-centered strategies, such as project-based and problem-based learning, as well as other context-responsive approaches. The development of adaptive learning models that address both teacher and student needs led to improvements in average student achievement and higher completion rates of learning materials. The findings suggest that instructional quality in VHS, particularly in agribusiness, can be strengthened through the systematic application of reflective learning models grounded in classroom action research. Teachers should emphasize the development of classroom action research competencies to enable prospective teachers to diagnose instructional challenges and implement evidence-based solutions effectively.